Trade Insulation as Social Protection - Do, Quy-Toan (The World Bank, 2013)
In a world with volatile food prices, countries have an incentive to shelter their populations from induced real income shocks. When some agents are net food producers while others are net consumers, there is scope for insurance between the two groups. A domestic social protection scheme would therefore transfer resources away from the former group to the latter in times of high food prices, and do the reverse otherwise. This paper shows that in the presence of consumer preference heterogeneity, implementing the optimal social protection policy can potentially induce higher food price volatility. Such policy indeed generates a counter-cyclical demand shock that amplifies the effects of the underlying food shortage. The results call for a reassessment of food stabilization policies. In particular, the authors urge caution against the systematic condemnation of trade insulation practices